Leukemic blast cells and controversies in models of hematopoiesis - Gluzman, D.F.; Sklyarenko, L.M.; Zavelevich, M.P.; Koval, S.V.; Ivanivskaya, T.S. (Experimental Oncology, 2015)
Classical and up-to-date models of hematopoietic lineage determination are briefly reviewed with the focus on myeloid-based models challenging the existence of the common progenitor for T cells, B cells and NK cells. The analysis of immunophenotype of leukemic blast cells seems to be a promising approach for interpreting some controversies in the schemes of normal hematopoiesis. The literature data as well as our own findings in the patients with various types of acute leukemias are in favor of the concept postulating that common myeloid-lymphoid progenitors giving rise to T and B cell branches retain the myeloid potential. The similarity of some immunophenotypic features of blast cells in pro-B acute lymphoblastic leukemia and acute monoblastic leukemia is consistent with monocyte origin postulated in the studies of normal hematopoiesis. Study of acute leukemias may be the challenging area of research allowing for new insight into the origin of hematopoietic cell lineages. Key Words: models of hematopoiesis, leukemic stem cell, immunophenotype, acute leukemias.